Creating language spaces with bilingual youth to expand conversations about students' communities and civic experiences - Ramirez, Pablito; Jaffee, Ashley Taylor (International journal of bilingual education and bilingualism, 2022)
This qualitative study investigated the ways in which one secondary social studies teacher engaged bilingual youth through translanguaging and citizenship education. We employed a translanguaging framework (García 2014) to document the ways in which a ninth grade bilingual teacher created language spaces with students. This study demonstrates the creative manner in which one social studies teacher used students' full linguistic repertoire to shape classroom instruction and advance conversations about community empowerment, civic life, social studies, and Latinx leadership.